If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -12) = 51 Reorder the terms: 3(-12 + x) = 51 (-12 * 3 + x * 3) = 51 (-36 + 3x) = 51 Solving -36 + 3x = 51 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 3x = 51 + 36 Combine like terms: -36 + 36 = 0 0 + 3x = 51 + 36 3x = 51 + 36 Combine like terms: 51 + 36 = 87 3x = 87 Divide each side by '3'. x = 29 Simplifying x = 29
| 2x-45435=3523523 | | 8u+2u-3u= | | 8x-5-3x=-6 | | 4x+1-2+2x=5x+7-3x | | 3-5x=2x-4 | | 6y-4+y= | | 9(-9)= | | -7a+4+8a=11-2 | | 10x-17=6x+13 | | 27-32= | | 6y-(-6)=12 | | 10-6x=70 | | 6=x+.7 | | 3x-2=4x+8 | | 81+(-15)= | | 2c-2(5c-6)-3(2c-6)+5c-5=0 | | 3-y= | | 8(2x-18)=9(2x-18) | | -6x^2+7x+10=0 | | 4x+x+9=45 | | 4.2x-3=0.5(8.4x+6) | | 41n+8=49n+42 | | 3(b+8)=-48 | | 7+6x+x=70 | | 4x+x*x+12-4+2x= | | .42857w-11=-.57143w | | -6x+7+4x=-1 | | 4+n= | | 7+.14x=8 | | 10y^2=16y-5 | | 10y^2=16y-5 | | 10y^2=16y-5 |